THE IMPORTANCE OF THE ENGLISH LANGUAGE IN MODERN EDUCATION. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
English has become one of the most influential languages in modern education, shaping the way students access knowledge, communicate globally, and prepare for their professional careers. As globalization continues to transform societies, the demand for English proficiency has significantly increased, particularly in developing countries like Uzbekistan. The main aim of this article is to examine the importance of English in modern education and to evaluate its impact on academic achievement, career opportunities, and personal development. The research methodology is based on a literature review of reports from UNESCO, the British Council, and other international organizations, combined with an analysis of local educational practices. In addition, observations and experiences of university students and students from underserved villages in Uzbekistan were considered to provide a regional perspective. The findings demonstrate that English plays a central role in four key areas: facilitating international communication, granting access to scientific and digital knowledge, improving employability, and enabling participation in global exchange programs. At the same time, the study highlights challenges such as unequal access to English education in rural regions and limited technological resources. English should not be viewed merely as a foreign language subject but as an essential tool for academic and professional growth in the 21st century. Addressing existing barriers will ensure that English education becomes more inclusive and beneficial for all learners. English has become one of the most influential languages in modern education, shaping the way students access knowledge, communicate globally, and prepare for their professional careers. As globalization continues to transform societies, the demand for English proficiency has significantly increased, particularly in developing countries like Uzbekistan. The main aim of this article is to examine the importance of English in modern education and to evaluate its impact on academic achievement, career opportunities, and personal development. The research methodology is based on a literature review of reports from UNESCO, the British Council, and other international organizations, combined with an analysis of local educational practices. In addition, observations and experiences of university students and students from underserved villages in Uzbekistan were considered to provide a regional perspective. The findings demonstrate that English plays a central role in four key areas: facilitating international communication, granting access to scientific and digital knowledge, improving employability, and enabling participation in global exchange programs. At the same time, the study highlights challenges such as unequal access to English education in rural regions and limited technological resources. English should not be viewed merely as a foreign language subject but as an essential tool for academic and professional growth in the 21st century. Addressing existing barriers will ensure that English education becomes more inclusive and beneficial for all learners.